Multicultural Quality of Life: experiences of a South Australian Muslim community amid the COVID-19 pandemic - Helen Jaqueline McLaren; Michelle Jones; Emi Patmisari (Indonesian Journal of Islam and Muslim Societies, 2023)
Muslims have a strong sense of obligation in which Islam informs their ways of life. As a religious minority within Australia, these obligatory practices may not be well understood by mainstream policy, health, and welfare services. This mixed-method, cross-sectional study assessed the self-reported quality of life (QoL), worldviews, and subjective experiences of religiosity and/or cultural identity of adults from a Muslim community affiliated with the Adelaide Mosque, metropolitan South Australia. Data were collected during the COVID-19 pandemic using the Multicultural Quality of Life Index (MQLI) and focus group discussions. Survey results (n = 98) showed women had lower MQLI scores than men did, and married participants had better MQLI scores than not-married did. Focus group participants (n = 18) reported feeling overwhelmed and isolated due to social distancing requirements during the COVID-19 pandemic, compounded by a lack of available ‘Muslim-friendly’ social support services. While results do not represent all Muslim perspectives in Australia, they reveal a dialogic interchange between gender and matrimonial differences, and cultural variances that may exist in the concept of wellbeing. Greater opportunities for social support integrating Muslim religiosity and culture in multicultural practice, in discrete and mainstream services, would benefit this South Australian community.